2009
DOI: 10.1080/13803390802169067
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of driving ability and the decision to resume driving following stroke

Abstract: The decision to resume driving after stroke can be complicated by the sequelae of stroke as well as the established finding that even healthy adults overestimate their driving ability. This study evaluated whether stroke survivors (n = 67) disproportionately overestimated their driving ability as compared to healthy significant others (n = 67). Comparison to a known target reduced self-bias among both groups, but shift toward enhanced accuracy was significantly greater among survivors than significant others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…Similar findings were reported among older drivers despite having had a previous adverse driving event or being independently judged as having driving difficulties (Marottoli & Richardson, 1998). Interestingly, this phenomenon has even been observed in stroke survivors who had not returned to drive post-stroke (Scott et al, 2009). Discrepancy between the stroke or brain-injured person's rating of their own driving ability and that of a driving therapist, health-care professional, or significant other, have been reported in the literature (Heikkila et al, 1999;Lundqvist & Alinder, 2007).…”
Section: Introductionsupporting
confidence: 66%
“…Similar findings were reported among older drivers despite having had a previous adverse driving event or being independently judged as having driving difficulties (Marottoli & Richardson, 1998). Interestingly, this phenomenon has even been observed in stroke survivors who had not returned to drive post-stroke (Scott et al, 2009). Discrepancy between the stroke or brain-injured person's rating of their own driving ability and that of a driving therapist, health-care professional, or significant other, have been reported in the literature (Heikkila et al, 1999;Lundqvist & Alinder, 2007).…”
Section: Introductionsupporting
confidence: 66%
“…Self-monitoring is an important moderator of risk associated with impairment in cognitive and motor domains: Individuals who have substantial risk factors for accidents, such as cognitive or physical impairments, may be at lower risk if they recognize and appreciate the nature of their deficits and compensate accordingly by changing their behavior (Anstey, Wood, Lord, & Walker, 2005;Rapport et al, 1993;Schanke & Sundet, 2000). For example, many stroke survivors who drive reduce their risk of accident by compensating for residual impairments via strategically limiting their exposure (e.g., avoiding night driving, heavy traffic, and long trips; Fisk, Owsley, & Mennemeier, 2002;Mackenzie & Paton, 2003;Scott et al, 2007). Similar findings have been supported for healthy older drivers (Ball et al, 1998;Daigneault, Joly, & Frigon, 2002;Lyman, McGwin, & Sims, 2001;Marottoli et al, 1993;Owsley & McGwin, 2003;Owsley, Stalvey, Wells, & Sloane, 1999) and among individuals with Alzheimer's disease (Hunt, Morris, Edwards, & Wilson, 1993).…”
Section: Awareness Of Deficit and Driving Riskmentioning
confidence: 98%
“…Additionally, ratings of current driving ability and driving safety are obtained via 5-point scales (e.g., poor, worse than average, average, better than average, excellent) by both the patient and their significant other. Although the DS has not been used in MS research, it has been shown to be reliable and valid among populations such as cognitively impaired persons with HIV (Marcotte et al, 2000), TBI (Rapport et al, 2006), and stroke (Scott et al, 2007). The survey was administered as a semistructured interview.…”
Section: Driving Survey (Ds)mentioning
confidence: 99%
“…Los sujetos mayores de 65 años que han padecido un ictus presentan un mayor riesgo de estar involucrados en accidentes mientras conducen, independientemente de la medicación que tomen si son comparados con otras patologías crónicas (cáncer, diabetes, artritis, deterioro cognitivo y glaucoma, entre otras) 8 . De modo que es de vital importancia conocer a los sujetos que han padecido un ictus que no deben conducir, más aún cuando se ha demostrado que los sujetos afectados por un ictus y sus familiares tienden a sobreestimar su capacidad de conducción 9 .…”
Section: Introductionunclassified